The Effect of Force on Fingerprint Image Quality and Fingerprint Distortion - Lidong Wang (International Journal of Electrical and Computer Engineering (IJECE), 2013)
The purpose of this paper is to investigate fingerprint quality and quality problems due to nonlinear elastic distortion. The effect of force on fingerprint quality was studied using computation and analysis of the correlation coefficient r between the fingerprint quality score and force. The correlation analysis results show that fingerprint quality is significantly attributed to force. Based on the U test, a comparative study between male and female students about the fingerprint quality was conducted. At the 0.05 level of significance, there is a significant difference between male and female students in the fingerprint quality of the flat left thumb at a greater force level and in the fingerprint quality of the slap left fingers at all force levels.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2489